THE EFFECTIVENESS OF THE DEPARTMENT OF WOMEN EMPOWERMENT AND CHILD PROTECTION, FAMILY PLANNING SIDOARJO DISTRICT IN PRESSING VIOLENCE OF WOMEN AND CHILDREN IN SIDOARJO DISTRICT - Anisa Sitta Ramadhani; Agus Widiyarta (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
The Office of Women's Empowerment, Child Protection, Family Planning is an organization in the administration of government affairs in the field of women's empowerment and child protection, in the field of population control and family planning (DP3AKB). as well as co-administration tasks. The research objective was to describe and analyze the effectiveness of DP3AKB Sidoarjo Regency in reducing the number of violence against women and children in Sidoarjo Regency which is still a lot. Effectiveness was assessed by the 7 dimensions of Gibson using a descriptive qualitative method. The technique of collecting data by interview, observation, and documentation, while the technique of interactive data analysis. The results showed that the DP3AKB Sidoarjo Regency has been effective in dealing with the number of violence in Sidoarjo Regency. However, this effort still lacks support from the people of Sidoarjo. Many reports of violence against women and children have come in. This reflects the lack of public awareness of the meaning of gender equality which is the goal of the Sidoarjo DP3AKB itself. In addition, in implementing the program, there are still many obstacles ranging from time and budget constraints from Covid handling orders which resulted in the suboptimal implementation of activities.